Studi analisis kesulitan siswa kelas VII SMPN 5 pasirkuda berdasarkan tahapan kastolan dalam menyelesaikan soal himpunan - Silpiani; Senjayawati, Eka (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study is a descriptive qualitative research for the purpose of analyzing errors and explaining the types of mistakes made by students when solving problems based on the text format provided. This research was conducted at a tertiary institution in Cianjur, with 10 research subjects in class VII B in the odd semester of the 2022/2023 academic year at SMP Negeri 5 Pasirkuda. The data collection method in this study was in the form of a written test. Based on the data presentation, the student error rate is 1) conceptual error, namely 66.9% with a "high" error percentage; 2) 10% procedural errors with a percentage of "very low" error categories; 3) 22.1% technical failure with a "low" failure percentage rate. Therefore, we can conclude that the conceptual understanding of student set material is relatively low. Therefore, the teacher should pay attention to students' conceptual understanding of the overall concept of the material and show students the important parts of the whole concept.